Composite silicon negative pole piece, preparation method thereof and sulfide all-solid-state battery

Through the use of composite silicon -negative chips in the full solid -state battery of sulfide, combined with the characteristics of porous silicon carbon and nano -silicon, it solves the problem of the problem of high -energy density and cycle stability, and achieves high -efficiency and safe battery performance. Essence

CN119381409AInactive Publication Date: 2025-01-28SHENZHEN SOLID ADVANCED MATERIALS TECH CO LTD

Patent Information

Application Number
CN202411944217.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In existing sulfide all-solid state batteries, it is difficult for silicon-based negative electrodes to take into account high energy density and cycle stability, and the preparation method has problems of high cost and unstable material performance.

Method used

The composite silicon negative chip is used to form a uniform composite silicon negative powder through the process of mixing the porous silicon carbon and nano -silicon in a specific proportion, and to form a uniform composite silicon negative powder, combined with sulfide solid -state electrolyte, to prepare a full solid -state battery of sulfide.

Benefits of technology

Achieve high -energy density and good cycle stability, reduce preparation costs, and improve the safety and mechanical stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381409A_ABST
    Figure CN119381409A_ABST
Patent Text Reader

Abstract

The invention relates to a composite silicon negative pole piece, a preparation method thereof and a sulfide all-solid-state battery. The preparation method of the composite silicon negative electrode plate comprises the following steps: providing composite silicon negative electrode powder which comprises the following components in parts by weight: 50-100 parts of porous silicon carbon and 50-100 parts of nano silicon; weighing porous silicon carbon and nano silicon, and premixing in a mortar to obtain a composite silicon negative electrode powder primary material; placing the composite silicon negative electrode powder primary material in a planetary ball mill for ball milling and mixing to obtain composite silicon negative electrode powder; the composite silicon negative electrode powder and a conductive agent are placed in a mortar to be premixed, then a binder is added, the mixture is transferred into a homogenizer, and uniform slurry is obtained after homogenization; and coating a current collector with the slurry, transferring into a blast oven for pre-drying, transferring into a vacuum oven, and drying to obtain the composite silicon negative pole piece. The composite silicon negative electrode plate provided by the invention has high specific capacity and good cycle stability, and can significantly improve the energy density and the cycle life of the sulfide all-solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a composite silicon negative electrode plate and a preparation method thereof, and a sulfide all-solid-state battery. Background Art

[0002] At present, there are many commonly used negative electrodes in sulfide all-solid-state batteries. One is the sulfide all-solid-state battery using porous silicon carbon as the negative electrode. Due to the rich pore structure inside the porous carbon, it can significantly accommodate the volume expansion of silicon during the cycle, so it has good cycle stability, but the addition of carbon reduces the nominal specific capacity of the material. At the same time, during the first cycle, the reaction between carbon and sulfide will significantly reduce the first coulomb efficiency of the material, and the rate performance still has room for improvement. The second is to use nano-silicon as the negative electrode. The prepared all-solid-state battery has a theoretical specific capacity of up to 3579mAh / g at room temperature, but nano-silicon is very easy to agglomerate, and there are many oxide layers on the surface. In addition, due to the inherent volume expansion of silicon, a large number of cracks will appear inside the electrode after the cycle, and it is impossible to maintain excellent cycle stability. At the same time, due to the low tap density, it is difficult to achieve a high volume energy density.

[0003] Existing patent 1 (patent application number: CN202410547109.0) discloses: a micron silicon negative electrode and its application in sulfide all-solid-state batteries. The preparation component of the micron silicon negative electrode of the present invention is micron silicon negative electrode powder; the preparation method of micron silicon negative electrode powder includes the following steps: placing crystalline silicon powder in a water vapor atmosphere and allowing it to oxidize to obtain micron silicon negative electrode powder. The micron silicon negative electrode of the present invention is a silicon negative electrode material dominated by crystalline silicon, and the material also contains a three-dimensional network of silicon oxygen (SiO x ) structure, the silicon-oxygen structure will form lithium silicate and lithium oxide during the lithiation process, which inhibits the volume expansion of crystalline silicon, thereby avoiding the serious volume expansion problem of crystalline silicon, effectively inhibiting the rapid attenuation of the full battery capacity, and ensuring the high efficiency and long cycle of the battery. In addition, the preparation cost of the present invention is low and can be mass-produced.

[0004] However, the micron silicon negative electrode powder prepared by this method is oxidized in a water vapor atmosphere, and the degree of oxidation is uncontrollable, which cannot ensure that the high capacity advantage of silicon can be effectively utilized.

[0005] Existing patent 2 (patent application number: CN202110991400.3) discloses: a sulfide silicon-based negative electrode sheet and its preparation method, and an all-solid-state lithium-ion battery. The preparation method comprises: step S1, mixing graphite, a first conductive agent, a first binder, and a first solvent to form a graphite slurry; coating the graphite slurry on the negative electrode collector layer, and then sequentially performing a first drying and a first hot rolling to form a graphite buffer layer on the negative electrode collector layer; step S2, mixing silicon material, sulfide electrolyte, a second conductive agent, a second binder, and a second solvent to form a silicon-based active slurry; coating the silicon-based active slurry on the surface of the graphite buffer layer away from the negative electrode collector layer, and then sequentially performing a second drying and a second hot rolling to obtain a silicon-based negative electrode sheet. The present invention effectively improves the problem in the prior art that it is difficult for silicon-based negative electrode sheets to simultaneously take into account high gram capacity and cycle performance.

[0006] However, the sulfide silicon-based negative electrode sheet prepared by this method preferentially forms a graphite buffer layer on the current collector, and the gram capacity of the prepared battery is extremely low (discharge capacity is less than 200 mAh / g).

[0007] In order to realize the industrial application of silicon-based negative electrodes in sulfide solid-state batteries in the existing technology, it is required that the silicon-based negative electrodes adapted to the sulfide solid electrolyte can have both high energy density and cycle stability. Therefore, the existing technology needs to be improved. Summary of the invention

[0008] In the prior art, in order to realize the industrial application of silicon-based negative electrodes in sulfide solid-state batteries, it is required that the silicon-based negative electrodes adapted to the sulfide solid electrolyte have both high energy density and cycle stability. Therefore, the present invention provides a composite silicon negative electrode pole piece and a preparation method thereof, and a sulfide all-solid-state battery.

[0009] To achieve the above object, in a first aspect, the present invention provides a method for preparing a composite silicon negative electrode sheet, which comprises the following steps: S11, providing a composite silicon negative electrode powder, comprising 50 to 100 parts by weight of porous silicon carbon and 50 to 100 parts by weight of nano silicon; S12, weighing the porous silicon carbon and nano-silicon according to a weight ratio, and premixing them in a mortar to obtain a composite silicon negative electrode powder preliminary material; S13, placing the composite silicon negative electrode powder raw material in a planetary ball mill for ball milling and mixing to obtain composite silicon negative electrode powder; S14, placing the composite silicon negative electrode powder and the conductive agent in a mortar for premixing, adding a binder, transferring the mixture into a homogenizer, and obtaining a uniform slurry after homogenization; S15, coating the slurry on the current collector, transferring it into a blast oven for pre-drying, transferring it into a vacuum oven for drying to obtain the desired composite silicon negative electrode sheet.

[0010] In one implementation, in S11, the silicon content of the porous silicon carbon is 30% to 70%, the theoretical specific capacity is 1300 to 2600 mAh / g, and the particle size is 1-30 um; the particle size of the nano silicon is 50 nm to 200 nm, and its tap density is 0.05 g / cm2 to 0.20 g / cm2.

[0011] In one implementation, in S3, the ball-to-material ratio during ball milling is 1:(1-20), the rotation speed is 50 r / min-300 r / min, and the ball milling time is 1-6 h.

[0012] In one implementation, in S14, the conductive agent is any one or more of conductive carbon black, acetylene black, vapor-grown carbon fiber, carbon nanotubes and Ketjen black; the binder is any one or more of polyvinylidene fluoride, polyacrylic acid, polyacrylonitrile, carboxymethyl cellulose and polytetrafluoroethylene.

[0013] In one implementation, in S14, the mass ratio of the composite silicon negative electrode powder, the conductive agent and the binder is (80-95):5:(1-15).

[0014] In one implementation, in S15, the coating thickness of the slurry is 40-110 um, and the drying temperature of the composite silicon negative electrode sheet is 70-100°C.

[0015] In a second aspect, the present invention further provides a composite silicon negative electrode plate, which is prepared by the above-mentioned method for preparing the composite silicon negative electrode plate.

[0016] In a third aspect, the present invention also provides a sulfide all-solid-state battery, which includes the above-mentioned composite silicon negative electrode plate.

[0017] In one implementation, the sulfide all-solid-state battery further includes a sulfide solid electrolyte, and the sulfide solid electrolyte includes Li6PS5Cl, Li3PS4, Li4SnS4 and Li7P3S 11 Any one of .

[0018] In one implementation, the method for preparing the sulfide all-solid-state battery comprises the following steps: S21, weighing an appropriate amount of sulfide solid electrolyte, putting it into a solid-state battery mold, and cold pressing it at a pressure of 200-400 MPa; S22, attaching the composite silicon negative electrode plate to one side of the sulfide solid electrolyte, and cold pressing the two to make them tightly bonded, wherein the cold pressing pressure is 200-400 MPa; S23, attaching a lithium sheet and an indium sheet to the side of the sulfide solid electrolyte away from the composite silicon negative electrode sheet in sequence, then placing a copper current collector, and cold pressing to make the lithium and indium tightly combined and in close contact with the sulfide solid electrolyte, wherein the cold pressing pressure is 100-300 MPa; S24, tighten the screws to ensure the operating external pressure of the all-solid-state battery to obtain the sulfide all-solid-state battery, wherein the operating external pressure of the sulfide all-solid-state battery is 30-100 MPa.

[0019] Beneficial effects: In the present invention, nano-silicon is embedded into the gaps of micron-sized porous silicon-carbon particles through planetary ball milling, which is beneficial to electrochemical sintering during the charge and discharge process, forming a complete glassy structure, and facilitating the transmission of lithium ions; by using sulfide solid electrolyte and composite silicon negative electrode material, higher ion conductivity and specific capacity are achieved, which helps to improve the energy density of the battery, so that it can store more energy per unit volume or weight, and combined with the rich pore structure inside the porous carbon in the composite silicon negative electrode material, it can significantly accommodate the volume expansion of silicon during the cycle, and has good cycle stability, providing a sulfide all-solid-state battery that achieves high energy density while ensuring cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a flow chart of the steps of the method for preparing the composite silicon negative electrode sheet provided by the present invention; Figure 2 Mechanism diagram of the composite silicon negative electrode provided by the present invention; Figure 3 It is a comparison chart of the cycle curves of the batteries prepared in Examples 1 to 5 and Comparative Examples 1 to 2 provided by the present invention; Figure 4 It is the SEM picture of the active material of Example 4 and Comparative Examples 1 and 2 provided by the present invention; The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the description of the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" described below means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms is not necessarily for the same embodiment or example. Moreover, the technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0022] See also Figure 1 , Figure 1 The present invention provides a method for preparing a composite silicon negative electrode sheet, which comprises the following steps: S11, providing a composite silicon negative electrode powder, comprising 50 to 100 parts by weight of porous silicon carbon and 50 to 100 parts by weight of nano silicon; S12, weighing the porous silicon carbon and nano-silicon according to a weight ratio, and premixing them in a mortar to obtain a composite silicon negative electrode powder preliminary material; S13, placing the composite silicon negative electrode powder raw material in a planetary ball mill for ball milling and mixing to obtain composite silicon negative electrode powder; S14, placing the composite silicon negative electrode powder and the conductive agent in a mortar for premixing, adding a binder, transferring the mixture into a homogenizer, and obtaining a uniform slurry after homogenization; S15, coating the slurry on the current collector, transferring it into a blast oven for pre-drying, transferring it into a vacuum oven for drying to obtain the desired composite silicon negative electrode sheet.

[0023] Specifically, in S11, the silicon content of the porous silicon carbon is 30% to 70%, the theoretical specific capacity is 1300 to 2600 mAh / g, and the particle size is 1-30um; the particle size of the nano silicon is 50nm to 200nm, and its tap density is 0.05g / cm2 to 0.20g / cm3. By providing 50 to 100 parts of porous silicon carbon and 50 to 100 parts of nano silicon in S11, the composition of the composite silicon negative electrode powder can be flexibly adjusted to optimize the electrochemical performance. Among them, porous silicon carbon provides higher conductivity and mechanical stability, while nano silicon helps to improve the specific capacity and reaction activity. Compared with common silicon negative electrode materials, this solution can better balance the conductivity and specific capacity by adjusting the ratio of porous silicon carbon and nano silicon, reduce the mechanical stress caused by the volume expansion of silicon during charging and discharging, and thus improve the cycle performance and stability of the battery.

[0024] Specifically, in S13, the ball-to-material ratio during ball milling is 1: (1-20), the rotation speed is 50r / min-300r / min, and the ball milling time is 1-6h. In the present invention, by adopting ball milling for mixing and optimizing the parameters of ball milling mixing, it is possible to ensure the uniform mixing of the composite silicon negative electrode powder and improve the uniformity and consistency of the material. In another embodiment, the present invention can also transfer the composite silicon negative electrode powder obtained in step S12 to a high-energy mechanical alloying device, such as a high-energy ball mill. When a high-energy ball mill is used for mixing, the ball-to-material ratio is 1: (10-30), the rotation speed is 300r / min-600r / min, the alloying time is 1-5h, and it is carried out under the protection of an inert gas (such as argon) to prevent oxidation of the material.

[0025] By combining S12 and S13, the porous silicon carbon and nano-silicon can be fully mixed through mortar pre-mixing and planetary ball milling mixing to form a uniform composite silicon negative electrode powder, which helps to ensure the consistency of the electrochemical performance of the electrode material during the charge and discharge process.

[0026] In S14, the conductive agent is any one or more of conductive carbon black, acetylene black, vapor-grown carbon fiber, carbon nanotubes and Ketjen black; the binder is any one or more of polyvinylidene fluoride, polyacrylic acid, polyacrylonitrile, carboxymethyl cellulose and polytetrafluoroethylene. Furthermore, the mass ratio of the composite silicon negative electrode powder, the conductive agent and the binder is (80~95):5:(1~15). In the present invention, by controlling the coating thickness and the drying temperature, the uniformity and density of the pole piece are ensured, while the thermal degradation of the material that may be caused by high-temperature drying is avoided, thereby improving the quality and performance of the pole piece.

[0027] Specifically, in S15, the coating thickness of the slurry is 40-110 um, and the drying temperature of the composite silicon negative electrode sheet is 70-100°C.

[0028] The high specific capacity and good cycle stability of the composite silicon negative electrode provided by the present invention can significantly improve the energy density and cycle life of lithium-ion batteries. The high capacity characteristics of silicon enable the battery to store more energy per unit weight and volume, while the introduction of porous structure and carbon material solves the problem of battery performance degradation caused by volume expansion of silicon materials during charging and discharging. At the same time, the buffering effect of the conductive network and porous structure of the carbon material reduces the pulverization and shedding of the electrode material, reduces the risk of internal short circuit, and thus improves the safety of the battery.

[0029] The present invention also provides a sulfide all-solid-state battery, which includes the above-mentioned composite silicon negative electrode plate. Specifically, the sulfide all-solid-state battery also includes a sulfide solid electrolyte, and the sulfide solid electrolyte includes Li6PS5Cl, Li3PS4, Li4SnS4 and Li7P3S 11 Any one of .

[0030] Furthermore, the preparation method of the sulfide all-solid-state battery comprises the following steps: S21, weighing an appropriate amount of sulfide solid electrolyte, putting it into a solid-state battery mold, and cold pressing it at a pressure of 200-400 MPa; S22, attaching the composite silicon negative electrode plate to one side of the sulfide solid electrolyte, and cold pressing the two to make them tightly bonded, wherein the cold pressing pressure is 200-400 MPa; S23, attaching a lithium sheet and an indium sheet to the side of the sulfide solid electrolyte away from the composite silicon negative electrode sheet in sequence, then placing a copper current collector, and cold pressing to make the lithium and indium tightly combined and in close contact with the sulfide solid electrolyte, wherein the cold pressing pressure is 100-300 MPa; S24, tighten the screws to ensure the operating external pressure of the all-solid-state battery to obtain the sulfide all-solid-state battery, wherein the operating external pressure of the sulfide all-solid-state battery is 30-100 MPa.

[0031] In the method provided by the present invention, since the all-solid-state battery uses a solid electrolyte, the risk of flammability and leakage of the liquid electrolyte is eliminated, and the safety of the battery is improved. The sulfide solid electrolyte generally has good chemical stability and thermal stability, which further enhances the safety performance of the battery. In addition, the flexibility of the sulfide electrolyte can buffer the volume change of the electrode material and improve the cycle life. By using a sulfide solid electrolyte and a composite silicon negative electrode material, higher ionic conductivity and specific capacity can be achieved, which helps to improve the energy density of the battery and store more energy per unit volume or weight. In general, the combination of a sulfide solid electrolyte and a composite silicon negative electrode in the present invention allows the battery to have better volume stability and cycle life during the charge and discharge process.

[0032] In addition, the preparation method realizes a close combination of the electrolyte and the electrode material through process steps such as cold pressing, simplifies the manufacturing process of the battery, and improves production efficiency. The preparation method provided by the present invention does not require high-temperature sintering or complex chemical treatment, reducing manufacturing costs. The cold pressing process used can make the battery components tightly combined, enhance the mechanical stability of the battery, reduce the interfacial impedance during use, and improve the stability of battery performance. By cold pressing, the various material layers are in close contact, the interfacial impedance is reduced, and the ion conduction efficiency of the battery is improved. Therefore, the sulfide all-solid-state battery provided by the present invention can adapt to more application scenarios, such as portable electronic devices, electric vehicles, and energy storage systems.

[0033] The present invention describes the technical solution of the present invention in detail through multiple embodiments and comparative examples.

[0034] Embodiment 1: The porous silicon carbon and nano-silicon were weighed in a weight ratio of 9:1 and pre-mixed in a mortar to obtain a preliminary material of composite silicon negative electrode powder; the preliminary material was placed in a planetary ball mill for ball milling mixing, and the ball milling conditions were a ball-to-material ratio of 5:1, a ball milling speed of 100 r / min, and a ball milling time of 2 h; and the composite silicon negative electrode powder was obtained.

[0035] The composite silicon negative electrode powder and the conductive agent Ketjen black are placed in a mortar according to a certain weight ratio for premixing, and then the binder polyvinylidene fluoride is added, and the mass ratio of the three is 90:5:5. The mixture is transferred to a homogenizer and a uniform slurry is obtained after homogenization. The slurry is coated on the current collector with a coating thickness of 50um, and then transferred to a blast oven to dry out most of the solvent, and then transferred to a vacuum oven at 80°C and dried to obtain a composite silicon negative electrode sheet.

[0036] Weigh an appropriate amount of sulfide solid electrolyte (Li6PS5Cl), put it into a solid-state battery mold, and cold press it into shape (pressure 300MPa); stick the composite silicon negative electrode plate to one side of the solid electrolyte, and cold press it to make the plate and the electrolyte tightly combined (pressure 300MPa); stick the lithium plate and indium plate to the other side of the solid electrolyte in sequence, and then put in the copper current collector, and cold press it to make the lithium and indium tightly combined and in close contact with the electrolyte (pressure 130MPa); tighten the screws to ensure the operating external pressure of the solid-state battery (pressure 65MPa).

[0037] Embodiment 2: The porous silicon carbon and nano-silicon were weighed in a weight ratio of 8:2 and pre-mixed in a mortar to obtain a preliminary material of composite silicon negative electrode powder; the preliminary material was placed in a planetary ball mill for ball milling and mixing, and the ball milling conditions were: ball-to-material ratio 5:1, ball milling speed 100 r / min, and ball milling time 2h; and the composite silicon negative electrode powder was obtained.

[0038] The composite silicon negative electrode powder and the conductive agent Ketjen black are placed in a mortar according to a certain weight ratio for premixing, and then the binder polyvinylidene fluoride is added, and the mass ratio of the three is 90:5:5. The mixture is transferred to a homogenizer and a uniform slurry is obtained after homogenization. The slurry is coated on the current collector with a coating thickness of 50um, and then transferred to a blast oven to dry out most of the solvent, and then transferred to a vacuum oven at 80°C and dried to obtain a composite silicon negative electrode sheet.

[0039] Weigh an appropriate amount of sulfide solid electrolyte (Li6PS5Cl), put it into a solid-state battery mold, and cold press it into shape (pressure 300MPa); stick the composite silicon negative electrode plate to one side of the solid electrolyte, and cold press it to make the plate and the electrolyte tightly combined (pressure 300MPa); stick the lithium plate and indium plate to the other side of the solid electrolyte in sequence, and then put in the copper current collector, and cold press it to make the lithium and indium tightly combined and in close contact with the electrolyte (pressure 130MPa); tighten the screws to ensure the operating external pressure of the solid-state battery (pressure 65MPa).

[0040] Embodiment 3: The porous silicon carbon and nano-silicon were weighed in a weight ratio of 7:3 and pre-mixed in a mortar to obtain a preliminary material of composite silicon negative electrode powder; the preliminary material was placed in a planetary ball mill for ball milling and mixing, and the ball milling conditions were: ball-to-material ratio 5:1, ball milling speed 100 r / min, and ball milling time 2 h; and the composite silicon negative electrode powder was obtained.

[0041] The composite silicon negative electrode powder and the conductive agent Ketjen black are placed in a mortar according to a certain weight ratio for premixing, and then the binder polyvinylidene fluoride is added, and the mass ratio of the three is 90:5:5. The mixture is transferred to a homogenizer and a uniform slurry is obtained after homogenization. The slurry is coated on the current collector with a coating thickness of 50um, and then transferred to a blast oven to dry out most of the solvent, and then transferred to a vacuum oven at 80°C and dried to obtain a composite silicon negative electrode sheet.

[0042] Weigh an appropriate amount of sulfide solid electrolyte (Li6PS5Cl), put it into a solid-state battery mold, and cold press it into shape (pressure 300MPa); stick the composite silicon negative electrode plate to one side of the solid electrolyte, and cold press it to make the plate and the electrolyte tightly combined (pressure 300MPa); stick the lithium plate and indium plate to the other side of the solid electrolyte in sequence, and then put in the copper current collector, and cold press it to make the lithium and indium tightly combined and in close contact with the electrolyte (pressure 130MPa); tighten the screws to ensure the operating external pressure of the solid-state battery (pressure 65MPa).

[0043] Embodiment 4: The porous silicon carbon and nano-silicon were weighed in a weight ratio of 6:4 and pre-mixed in a mortar to obtain a preliminary material of composite silicon negative electrode powder; the preliminary material was placed in a planetary ball mill for ball milling and mixing, and the ball milling conditions were: ball-to-material ratio 5:1, ball milling speed 100 r / min, and ball milling time 2 h; and the composite silicon negative electrode powder was obtained.

[0044] The composite silicon negative electrode powder and the conductive agent Ketjen black are placed in a mortar according to a certain weight ratio for premixing, and then the binder polyvinylidene fluoride is added, and the mass ratio of the three is 90:5:5. The mixture is transferred to a homogenizer and a uniform slurry is obtained after homogenization. The slurry is coated on the current collector with a coating thickness of 50um, and then transferred to a blast oven to dry out most of the solvent, and then transferred to a vacuum oven at 80°C and dried to obtain a composite silicon negative electrode sheet.

[0045] Weigh an appropriate amount of sulfide solid electrolyte (Li6PS5Cl), put it into a solid-state battery mold, and cold press it into shape (pressure 300MPa); stick the composite silicon negative electrode plate to one side of the solid electrolyte, and cold press it to make the plate and the electrolyte tightly combined (pressure 300MPa); stick the lithium plate and indium plate to the other side of the solid electrolyte in sequence, and then put in the copper current collector, and cold press it to make the lithium and indium tightly combined and in close contact with the electrolyte (pressure 130MPa); tighten the screws to ensure the operating external pressure of the solid-state battery (pressure 65MPa).

[0046] Embodiment 5: The porous silicon carbon and nano-silicon were weighed in a weight ratio of 5:5 and pre-mixed in a mortar to obtain a preliminary material of composite silicon negative electrode powder; the preliminary material was placed in a planetary ball mill for ball milling and mixing, and the ball milling conditions were: ball-to-material ratio 5:1, ball milling speed 100 r / min, and ball milling time 2 h; and the composite silicon negative electrode powder was obtained.

[0047] The composite silicon negative electrode powder and the conductive agent Ketjen black are placed in a mortar according to a certain weight ratio for premixing, and then the binder polyvinylidene fluoride is added, and the mass ratio of the three is 90:5:5. The mixture is transferred to a homogenizer and a uniform slurry is obtained after homogenization. The slurry is coated on the current collector with a coating thickness of 50um, and then transferred to a blast oven to dry out most of the solvent, and then transferred to a vacuum oven at 80°C and dried to obtain a composite silicon negative electrode sheet.

[0048] Weigh an appropriate amount of sulfide solid electrolyte (Li6PS5Cl), put it into a solid-state battery mold, and cold press it into shape (pressure 300MPa); stick the composite silicon negative electrode plate to one side of the solid electrolyte, and cold press it to make the plate and the electrolyte tightly combined (pressure 300MPa); stick the lithium plate and indium plate to the other side of the solid electrolyte in sequence, and then put in the copper current collector, and cold press it to make the lithium and indium tightly combined and in close contact with the electrolyte (pressure 130MPa); tighten the screws to ensure the operating external pressure of the solid-state battery (pressure 65MPa).

[0049] Comparative Example 1: Different from Example 1, in this comparative example, the initial material of silicon negative electrode powder is porous silicon carbon, and no nano-silicon is added. The other steps are the same as those in Example 1 and will not be repeated here.

[0050] Comparative Example 2: Different from Example 1, in this comparative example, the initial material of silicon negative electrode powder is nano-silicon, and no nano-silicon is added. The other steps are the same as those in Example 1 and will not be repeated here.

[0051] The present invention tests the electrochemical performance of the sulfide all-solid-state battery prepared above, and the results are shown in Table 1. Figure 3 and Figure 4 .

[0052] Table 1. Electrochemical performance test results of various sulfide all-solid-state batteries:

[0053] Refer to Table 1. Figure 2~Figure 4 ,in, Figure 2 The mechanism diagram of the composite silicon negative electrode provided by the present invention, Figure 3 is a comparison chart of the cycle curves of the batteries prepared in Examples 1 to 5 and Comparative Examples 1 to 2 provided by the present invention, Figure 4 It is the SEM picture of the active material of Example 4 and Comparative Examples 1 and 2 provided by the present invention. Specifically, Figure 4 The active materials in the anode are composite silicon powder, porous silicon carbon and nano silicon. Figure 2 The results show that the present invention embeds nano-silicon into the gaps of micron-sized porous silicon-carbon particles, which is beneficial to electrochemical sintering during the charge and discharge process, forming a complete glass structure, which is beneficial to the transmission of lithium ions. Figure 3 and Figure 4 As can be seen from Table 1, the sulfide all-solid-state battery made of the composite silicon negative electrode plate provided by the present invention is relative to the sulfide all-solid-state battery made of porous silicon carbon and nano-silicon. It combines porous silicon carbon and nano-silicon, so that nano-silicon enters the rich pore structure inside the porous silicon carbon. By combining nano-silicon with porous silicon carbon, the batteries of Examples 1 to 5 have higher first charge capacity and higher first coulomb efficiency than Comparative Example 1. At the same time, the batteries of Examples 1 to 5 have better cycle stability than Comparative Example 2, which can improve the mechanical stability and electrochemical properties of the electrode while having high energy density.

[0054] In summary, the technical solution provided by the present invention, by combining sulfide solid electrolyte and composite silicon negative electrode material, and the composite silicon negative electrode material is combined with porous silicon carbon and nano-silicon, can significantly improve the energy density, cycle stability, safety and operating temperature range of the battery, and has excellent application prospects.

[0055] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a composite silicon negative electrode sheet, characterized in that: The following steps are involved: S11, providing a composite silicon negative electrode powder, comprising 50 to 100 parts by weight of porous silicon carbon and 50 to 100 parts by weight of nano silicon; S12, weighing the porous silicon carbon and nano-silicon according to a weight ratio, and premixing them in a mortar to obtain a composite silicon negative electrode powder preliminary material; S13, placing the composite silicon negative electrode powder raw material in a planetary ball mill for ball milling and mixing to obtain composite silicon negative electrode powder; S14, placing the composite silicon negative electrode powder and the conductive agent in a mortar for premixing, adding a binder, transferring the mixture into a homogenizer, and obtaining a uniform slurry after homogenization; S15, coating the slurry on the current collector, transferring it into a blast oven for pre-drying, transferring it into a vacuum oven for drying to obtain the desired composite silicon negative electrode sheet.

2. The method for preparing a composite silicon negative electrode sheet according to claim 1, characterized in that: In S11, the silicon content of the porous silicon carbon is 30% to 70%, the theoretical specific capacity is 1300 to 2600 mAh / g, and the particle size is 1-30 um; the particle size of the nano silicon is 50 nm to 200 nm, and its tap density is 0.05 g / cm2 to 0.20 g / cm2.

3. The method for preparing a composite silicon negative electrode sheet according to claim 1, characterized in that: In S13, the ball-to-material ratio during ball milling is 1:(1-20), the rotation speed is 50 r / min-300 r / min, and the ball milling time is 1-6 h.

4. The method for preparing a composite silicon negative electrode sheet according to claim 1, characterized in that: In S14, the conductive agent is any one or more of conductive carbon black, acetylene black, vapor-grown carbon fiber, carbon nanotube and Ketjen black; the binder is any one or more of polyvinylidene fluoride, polyacrylic acid, polyacrylonitrile, carboxymethyl cellulose and polytetrafluoroethylene.

5. The method for preparing a composite silicon negative electrode sheet according to claim 1, characterized in that: In S14, the mass ratio of the composite silicon negative electrode powder, the conductive agent and the binder is (80-95):5:(1-15).

6. The method for preparing a composite silicon negative electrode sheet according to claim 1, characterized in that: In S5, the coating thickness of the slurry is 40-110 um, and the drying temperature of the composite silicon negative electrode sheet is 70-100°C.

7. A composite silicon negative electrode plate, characterized in that: It is prepared by the method for preparing the composite silicon negative electrode sheet according to any one of claims 1 to 6.

8. A sulfide all-solid-state battery, characterized in that: Including the composite silicon negative electrode plate as described in claim 7.

9. The sulfide all-solid-state battery according to claim 8, characterized in that: The sulfide all-solid-state battery also includes a sulfide solid electrolyte, which includes Li6PS5Cl, Li3PS4, Li4SnS4 and Li7P3S 11 Any one of .

10. The sulfide all-solid-state battery according to claim 8, characterized in that: The preparation method of the sulfide all-solid-state battery comprises the following steps: S21, weighing an appropriate amount of sulfide solid electrolyte, putting it into a solid-state battery mold, and cold pressing it at a pressure of 200-400 MPa; S22, attaching the composite silicon negative electrode plate to one side of the sulfide solid electrolyte, and cold pressing the two to make them tightly bonded, wherein the cold pressing pressure is 200-400 MPa; S23, attaching a lithium sheet and an indium sheet to the side of the sulfide solid electrolyte away from the composite silicon negative electrode sheet in sequence, then placing a copper current collector, and cold pressing to make the lithium and indium tightly combined and in close contact with the sulfide solid electrolyte, wherein the cold pressing pressure is 100-300 MPa; S24, tighten the screws to ensure the operating external pressure of the all-solid-state battery to obtain the sulfide all-solid-state battery, wherein the operating external pressure of the sulfide all-solid-state battery is 30-100 MPa.

Citation Information

Patent Citations

  • Sulfide silicon-based anode sheet and its preparation method, all-solid-state lithium-ion battery

    CN113764625B

  • Micron silicon negative electrode and application thereof in sulfide all-solid-state battery

    CN118472231A

  • Preparation method of silicon-carbon negative electrode material for high-compaction-density lithium ion battery

    CN108736007A

  • Porous silicon carbon-based composite material and preparation method thereof, negative electrode and lithium ion battery

    CN116779816A

  • All-solid-state battery silicon-based negative electrode, preparation method thereof and all-solid-state battery

    CN117577854A

Cited By

  • Silicon-carbon negative electrode material applied to sulfide solid-state battery and modification method of silicon-carbon negative electrode material

    CN120237195A